Ageing culturally significant relic trees in southeast Queensland to support bushfire management strategies. (9th April 2020) - Ngugi, Michael R.; Knight, Jon; Hua, Quan; Dowling, Ralph; Kington, David; Burns, Darren
Summary: Appropriate fire management strategies are needed to protect forests and large old ecologically and culturally significant trees in natural landscapes. The aim of this study was to determine the age of large old and relic trees of cultural significance that included Cypress Pine ( Callitris columellaris F. Muell.), a species that is sensitive to crown scorching fires in a fire‐prone landscape, and to calibrate a tree‐growth‐rate method for estimating tree age. Twelve large trees were dated using radiocarbon ( 14 C) dating. The trees are located on North Stradbroke Island (Indigenous name: Minjerribah), southeast Queensland (Australia) in a fire‐prone landscape where recent wildfires have destroyed many large trees. The median tree ages ranged from 155 to 369 years. These results suggest an important role of past Indigenous land management practices in protecting Cypress Pine from crown scorching fires. The tree‐growth‐rate‐based method for estimating tree age generally overestimated the age derived from radiocarbon dating. Bias correction factors were developed for correcting various measures of periodic growth rates. This study provides evidence that appropriate low‐intensity fire strategies have the potential to contribute to the survival of forests and conserve large old trees.